PENERAPAN MODEL PEMBELAJARAN JIGSAW PADA MATA PELAJARAN IPAS SISWA KELAS V SD NEGERI 1 TRIKOYO - Yonifah, Tantrie; Pestalozi, Donni; Aswarliansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the completeness of the science learning outcomes of fifth-grade students of SD Negeri 1 Trikoyo after the application of the Jigsaw learning model. This study used Pre-test and Post-test. Sampling was obtained from the population, the sampling technique in this study used saturated sampling. The instrument used was in the form of Multiple Choice with a total of 20 questions. The data analysis technique used the z-test at a significance level of a = 0.05. The results of the study obtained that Zhitung = 5.07> Ztabel = 1.64 so that it was proven that Ha was accepted and Ho was rejected. The Pancasila learning outcomes of fifth-grade students of SD Negeri 1 Trikoyo after the application of the Jigsaw learning model were significantly complete. The average value was 85.10 and the percentage of students who completed was 80.96%.